Duckweed untuk Kebaikan: Inovasi Pakan Ikan Hemat Ramah Lingkungan di Panti Asuhan Al Dzikro, Imogiri, Bantul, Yogyakarta - Desi Utami; Selvina Ratna Hayati; Fauziyah Yumna; Susanti Mugi Lestari; Ihza Farras Faadhilah; Samsuri Djamal; Dita Sari Alfiawati Husni; Leila Keumala Raseuki; Nasywa Atha'ala; Padia Desi Rahmawati; Hafsah Dwi Nur Haliza; Desy Putri Handayani (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2026)
Al Dzikro Orphanage in Imogiri, Bantul Regency, initiated a fish farming program to reduce the dependency on public donations. However, this program faced challenges due to the high cost of commercial fish feed. As an alternative, a community service team from the Faculty of Agriculture, Universitas Gadjah Mada (Faperta UGM), introduced duckweed usage as a sustainable feed source with high protein content. This program aimed to promote community participation in optimizing duckweed fermentation as fish feed and to strengthen collaboration between UGM and the local government. A participatory approach was implemented through duckweed cultivation training for the orphanage children, pretest and posttest evaluation, as well as laboratory fermentation tests by the team. The result from this community service shows that the participants successfully understood and applied small-scale duckweed cultivation sand its fermentation techniques. The evaluation indicated that the average posttest scores increased almost two fold from the pretest scores. Laboratory analysis demonstrated that the highest fermentation occurred in the duckweed and molasses treatment (P1) for Bacillus subtilis after 96 hours (8.46 Log CFU/mL), while Lactobacillus plantarum reached its highest growth in the duckweed, molasses, and Biokul treatment (P1) after 48 hours (6.97 Log CFU/mL). Besides the technical training, the service team also gave motivation about higher education, particularly in the agricultural field. This program includes a practical example of accessible agricultural innovation based on community-oriented activities and aligned with sustainable goals.